Analysis of Teacher Difficulties in Using Smart Board Technology in Primary School : A Case Study at SDN 2 Pilangsari - Fitryarany, Della (LEOTECH: Journal of Learning Education and Technology, 2025)
This study aims to analyze the challenges faced by teachers in utilizing Smart Board as a technology-based learning media at SDN 2 Pilangsari. The background of the research is based on the gap between the potential to increase students' learning motivation through technology and the implementation constraints in the field. Using a qualitative approach through in-depth interviews with teachers, the research revealed five main challenges: (1) limited teacher training, (2) lack of technical understanding, (3) lack of IT support, and (4) difficulty integrating technology with teaching materials (5) impact of student depence. The findings provide practical contributions in the form of recommendations for the development of more effective teacher training programs as well as policy implications in the provision of supporting infrastructure. Theoretically, this study enriches the literature on the adoption of educational technology in primary schools by emphasizing the aspect of teacher readiness as a critical factor for successful implementation.